Respuesta :
Answer:
x = 9.6
x = - 2.6
Step-by-step explanation:
[tex]x=\frac{-b±\sqrt{b^{2}-4ac } }{2a}[/tex]
Ignore the before the ± it wouldn't let me type it correctly.
x² - 7x - 25 = 0
a = 1
b = - 7
c = - 25
[tex]x=\frac{-(-7)±\sqrt{-7^{2}-4((1)(-25)) } }{2(1)}[/tex]
[tex]x=\frac{7±\sqrt{49-4((1)(-25)) } }{2(1)}[/tex]
[tex]x=\frac{7±\sqrt{49+100 } }{2(1)}[/tex]
[tex]x=\frac{7±\sqrt{149 } }{2}[/tex]
[tex]x=\frac{7±12.2}{2}[/tex]
Two separate equations
[tex]x=\frac{7+12.2}{2}[/tex]
[tex]x=\frac{7-12.2}{2}[/tex]
[tex]x=\frac{7+12.2}{2}[/tex]
[tex]x=\frac{19.2}{2}[/tex]
x = 9.6
[tex]x=\frac{7-12.2}{2}[/tex]
[tex]x=\frac{-5.2}{2}[/tex]
x = - 2.6
For this just use the quadratic formula to find the zeros. In this case, you get 7 +/- square root 149 over 2. Which gives you -2.6 and 9.6.